Pelaksanaan Model Pembelajaran Kepesantrenan Sebagai Pengembangan Karakter di Pesantren Moderen Datok Sulaiman Bagian Putra Kota Palopo - Mika; Zulkifli (South Sulawesi Education Development, 2024)
Abstract :This research aims to find out how the Islamic boarding school learning model is implemented as character development at the Datok Sulaiman Putra Modern Islamic Boarding School, Palopo City and to find out what the supporting and inhibiting factors are for the Islamic boarding school learning model as character development at the Datok Sulaiman Putra Modern Islamic Boarding School, Palopo City. The research results show that the implementation of the Islamic boarding school learning model at the Datok Sulaiman Putra Modern Islamic Boarding School, Palopo City is carried out at the start of Islamic boarding school learning hours. Islamic boarding school learning activities are programs that support the formation of better character values ​​for students, where students are taught to be obedient to worship, independent, disciplined, responsible, live simply, creatively and carry out various other activities or routines. Supporting factors include carrying out various student activities both in the teaching and learning process in Islamic boarding schools and outside Islamic boarding schools/Islamic boarding schools, where the environmental atmosphere in Islamic boarding schools can make students comfortable and safe in carrying out various activities or routines. The routines that students carry out in Islamic boarding schools are daily life habits such as prayer, fasting, reciting the Koran, good manners, maintaining cleanliness, etc. that will stick with the students.